Implicit attitudes towards exercise and physical activity behaviour among in-patients with psychiatric disorders. (October 2018) - Gerber, Markus; Ehrbar, Janine; Brand, Ralf; Antoniewicz, Franziska; Brand, Serge; Colledge, Flora; Donath, Lars; Egger, Stephan T.; Hatzinger, Martin; Holsboer-Trachsler, Edith; Imboden, Christian; Schweinfurth, Nina; et al.
Abstract: The current body of evidence suggests that in healthy participants, implicit attitudes towards physical activity explain variance in exercise behaviour beyond explicit cognitive processes. However, such relationships have not been examined in psychiatric patients, although this may contribute to a better understanding of the motivational and volitional resources needed to self-regulate their exercise behaviour. Therefore, the present cross-sectional study aimed to assess implicit attitudes towards exercise among psychiatric in-patients, and to correlate these implicit attitudes with their physical activity levels. Patients (N = 101) showing a psychiatric disorder, but no severe cognitive impairment, were directly recruited from psychiatric clinics. Their physical activity levels were assessed using both accelerometers and self-reports. Additionally, patients reported psychiatric symptoms and performed a single-target implicit association test (ST-IAT) with exercise employed as the target category. Of all patients, 39% showed a preference for exercise, whereas 13% showed an aversion towards exercise. The implicit attitudes of the remaining participants were equally strong for both concepts. Based on correlational analysis (correcting for age, sex, psychiatric symptoms severity, and ST-IAT sequence), no association was found between ST-IAT score, or self-reported and objectively assessed physical activity. Consequently, the link between exercise behaviour and implicit attitudes towards physical activity found in healthy participants could not be observed in psychiatric patients. Highlights: First study worldwide assessing implicit attitudes towards exercise in psychiatric patients. Physical activity assessed via self-reports and 7-day accelerometry. Implicit attitudes towards exercise assessed via single-target implicit association test (ST-IAT). No significant associations found between physical activity and implicit attitudes. Avenues for future research shown in this new area of psychiatric inquiry.